PEMANFAATAN LIMBAH PADAT PABRIK TAHU SEBAGAI PAKAN KONSENTRAT TERNAK DENGAN PROSES FERMENTASI - Joni Hermana (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
This research was aimed to determine fermentation influence to soya nutrition. The variations in this research were fermentation period (1 day, 2 days, 3 days, 4 days, 5 days and 6 days) and bio-N concentration (10 ml/2 kg soya waste, 20 ml/2kg tofu waste and 30 ml/2 kg tofu waste). The nutrition which examined with proksimat analysis were rough protein, rough fibre, extract non nitrogen (BETN), rough fat. The result showed that the optimum period of fermentation was 4 days and the effective bio-N concentration was 20 ml/2 kg tofu waste. The rough protein increased to 26,07%, and rough fat increased to 17,35%.